What shapes perceptions of climate change? New research since 2010. (11th November 2015) - Weber, Elke U.
Abstract : Five years ago, an article in the first issue of WIREs Climate Change reviewed the factors that shape perceptions of climate change. Climate change is an abstract statistical phenomenon, namely a slow and gradual modification of average climate conditions, and thus a difficult phenomenon to detect and assess accurately based on personal experience. The current update of the original article—'new research since 2010'—revisits topics covered in the original contribution: the role of personal experience with climate change, in particular extreme weather events; the effects of psychological distance on climate change perception and action; the effects of political ideology, age, gender, and nationality, and situational influences; and the role of different processing modes in climate change perception and the low level of visceral response (dread) associated with climate change risks. In addition, the current article also addresses new topics since 2010: attribute substitution or the use of weather anomalies—'local' warming or cooling—when judging the likelihood of global warming; the effects of different labels for the phenomenon—global warming versus climate change—on perceptions of its likelihood and importance; and the effect and role of uncertainty about different aspects of climate change and its consequences and how it is communicated on perceptions and actions. WIREs Clim Change 2016, 7:125–134. doi: 10.1002/wcc.377 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Perceptions of Climate Change